Pravi pasti globalizacije sta provincializem in neznanje - Svetličič, Marjan (Teorija in praksa, 1997)
A critical assessment of the book Traps of globalization by H.P.Martin and H. Schuman-a is indicates that globalisation is not a zero sum game as authors assume, neglecting law of comparative advantages. It is still very much valid particularly if taken together with the principle of compensation for those who are loosing from international trade or/and globalisation. Benefits of globalisation outrate costs. In spite of all costs it is welfare enhancing. Globalisation is bringing about a convergence among countries if they follow the right policies although it also contributes to the marginalisation of unskilled workers, reduction of their wages, their unemployment and social disintegration. But this is less to be attributed to globalisation and more to technical progress. The idealisation of the role of the government is also criticised. Market failures are still less dangerous that government failures.Governments can not set better exchange rates than market, as is suggested. Alarming the public about the negative consequences of globalisation is welcome although in parts the authors come almost close to the Marxist wrong predictions about the future of capitalism. But the proposals given in the book are not well founded, are not a solution to the problem. Lack of knowledge and provincialism are indicated as more dangerous traps of globalisation than those indicated by the authors.
Keywords: globalizacija; globalization; globalni razvoj; ekonomski razvoj; unemployment; brezposelnost; razslojevanje; ekonomska politika; svetovno gospodarstvo